(untitled) (Scientific journal of the Fergana State University, 2026)
The article evaluates gully erosion hazard in the Tashkent region using GIS and compares a Weighted Overlay model with a gully inventory derived from Google Earth Pro. Slope, flow accumulation and aspect extracted from a DEM are combined with 40–40–20% weights to map low, medium and high hazard zones. The high-hazard class captures about 78–82% of mapped gullies, providing a reliable basis for planning erosion control measures.